111k views
1 vote
Solve as a multistep equation 2x+4-5=3x+3

1 Answer

3 votes

To do this, first subtract 3x from both sides of the equation


\begin{gathered} 2x+4-5=3x+3 \\ 2x+4-5-3x=3x+3-3x \\ 2x+4-5-3x=3 \end{gathered}

Add similar terms to the left side of the equation


-x-1=3

Now add 1 to both sides of the equation


\begin{gathered} -x-1+1=3+1 \\ -x=4 \end{gathered}

Finally, multiply by -1 on both sides of the equation


-x\cdot-1=4\cdot-1

Therefore,


x=-4

User Logan Byers
by
4.7k points